Education Research: A case-based bioethics curriculum for neurology residents - Tolchin, Benjamin (Neurology, 2015)
BACKGROUND: In 2012, the American Academy of Neurology (AAN) updated and expanded its ethics curriculum into Practical Ethics in Clinical Neurology, a case-based ethics curriculum for neurologists. METHODS: We piloted a case-based bioethics curriculum for neurology residents using the framework and topics recommended by the AAN, matched to clinical cases drawn from Columbia's neurologic services. Our primary outcome was residents' ability to analyze and manage ethically complex cases as measured on precurriculum and postcurriculum multiple-choice quizzes. Secondary outcomes included precurriculum and postcurriculum self-assessed comfort in discussing and managing ethically complex cases, as well as attendance at ethics discussion sessions as compared to attendance at other didactic sessions. RESULTS: Resident performance on quizzes improved from 75.8% to 86.7% (p = 0.02). Comfort in discussing ethically complex cases improved from 6.4 to 7.4 on a 10-point scale (p = 0.03). Comfort in managing such cases trended toward improvement but did not reach statistical significance. Attendance was significantly better at ethics discussions (73.5%) than at other didactic sessions (61.7%, p = 0.04). CONCLUSION: Our formal case-based ethics curriculum for neurology residents, based on core topics drawn from the AAN's published curricula, was successfully piloted. Our study showed a statistically significant improvement in residents' ability to analyze and manage ethically complex cases as measured by multiple-choice tests and self-assessments.